Research protocol of a multifaceted prospective mixed-method longitudinal study: Navigating Through Life - Western Australian study of transitions from out-of-home care - Lauren Parsons; Donna Chung; Reinie Cordier; David Hodgson; Stephan Lund; Philip Mendes; Melissa O'Donnell; Richard Parsons; Stian Thoresen (BMC, 2020)
Abstract Background Developing robust evidence is a challenge for researchers working with disadvantaged or vulnerable populations. For example, research shows that young people who have transitioned from out-of-home care (OOHC) to independent adulthood often experience poor long-term outcomes. However, evidence for the aetiology of those outcomes is weak due to methodological limitations such as small sample sizes and a lack of longitudinal data. This paper details the protocol for Navigating Through Life, a study that utilises novel research methods to better understand the pathways and outcomes of young people as they leave OOHC in Western Australia (WA). Methods Navigating Through Life is a longitudinal, mixed methods, population-based study. A prospective longitudinal study of young people aged 15-25 years will follow participants' experiences and outcomes over a two-year period. Quantitative and qualitative data is being collected from participants five times over 2 years, using standardised outcome measures and individual interviews. Outcome measures focus on key dimensions of young people's lives (e.g., social inclusion, well-being, resilience, self-determination). Interviews examine important influences and the variable contexts into which young people have transitioned from care. In addition, retrospective population-level data for young people transitioning from OOHC will be obtained from linked Western Australian government administrative records. Using a multitude of data sources, analysis will map pathways and outcomes of young people with care experience, and comparisons will be made with other population groups within WA. Discussion Navigating Through Life exemplifies a novel utilisation of multiple data sources to research outcomes for vulnerable and difficult to reach populations, and offers insights for other complex mixed-methods longitudinal studies. Results will provide new and more comprehensive data about specific pathways that may be influential to a range of post-care outcomes. Findings will extend evidence to inform better service-delivery models that improve outcomes and reduce disparities for vulnerable young people.